Combined first-principles and EXAFS study of structural instability in BaZrO3 - A. I. Lebedev; I. A. Sluchinskaya (Journal of Advanced Dielectrics, 2015)
Phonon spectrum of cubic barium zirconate is calculated from first principles using the density functional theory. Unstable phonon mode with the R25 symmetry in the phonon spectrum indicates an instability of the cubic structure with respect to rotations of the oxygen octahedra. It is shown that the ground-state structure of the crystal is I4/mcm. In order to find the manifestations of the predicted instability, EXAFS measurements at the Ba LIII-edge are used to study the local structure of BaZrO3 at 300 K. An enhanced value of the Debye–Waller factor for the Ba–O atomic pair (σ12∼0.015Å2) revealed in the experiment is associated with the predicted structural instability. The average amplitude of the thermal rotations estimated from the measured σ12 value is ∼4° at 300 K. The closeness of the calculated energies of different distorted phases resulting from the condensation of the R25 mode suggests a possible formation of a quenched rotational disorder in BaZrO3 at low temperature, which can explain the discrepancy between the calculations and experiment.